The Role and Significance of Polish Local Governments in The Polish Circular Economy Model - Aneta TYLMAN; Marcin PODGÓRSKI; Agnieszka SKOCZYLAS-TWOREK; Ewa SZAFRAŃSKA (Communications of International Proceedings, 2022)
The purpose of this paper is to identify potential new elements that could motivate the local government to implement the circular economy idea. An essential component of that endeavor is preserving trust in the local entrepreneurial environment. According to the literature on the topic, local government is one of the Quadruple Helix players and serves as the foundation for the development of economic symbioses in the circular economy. Therefore, a clearer explanation of its function in this economy is essential. The survey approach and expert interviews were used in particular to examine how the smallest Polish local government entities - communes - envisage their future role in the development of the circular economy in Poland. The findings of the study show, among other things, that Polish local government units view their contribution to the growth of the circular economy as active. This position advances beyond the existing coordination of waste management operations and into the position of an active businessperson engaged in the secondary raw materials market.
Keywords: Local Government; Circular Economy; Sustainable Development